Effect of heat moisture treatment on physicochemical and pasting properties of starch extracted from eleven sweet potato varieties - Tsakama, M.; Mwangwela, A.M.; Manani, T.A.; Mahungu, N.M. (2011)
Starch separated from eleven sweet potato varieties was subjected to heat moisture treatment (HMT) at 30% moisture and 110°C for 3 hours. Following HMT, there were no significant changes in physicochemical properties of the starches. This was attributed to limited moisture content (30%) to influence hydration that could consequently alter granule morphology. Further, chemical parameters such as amylose content, pH and phosphorus were not affected because HMT is a physical treatment. In contrast, HMT caused changes in the packing arrangement of the polymer chains leading to enhanced intragranular binding. Alteration of the internal organisation of the granules caused significant changes in pasting properties of the starches such as pasting time, pasting temperature, peak viscosity, hot paste viscosity, cold paste viscosity, breakdown, set back and stability ratios. The findings provide evidence that functionality of sweet potato starch can be altered to suit a particular industrial need.